Investigating the effects of Magnesium Oxide Nanoparticle Toxicity on K562 Blood Type Cancer Cells - S Ansari Moghaddam; F Rahmani; N Delirezh (Armaghane Danesh Bimonthly Journal, 2017)
Abstract:   Background and aim: Cancer is a complex genetic disorder, which is mainly caused by environmental factors. Today nanoparticles are widely used in the field of medicine, pharmaceutical and cancer treatment. Magnesium oxide nanoparticle is one of the most important mineral oxides. The purpose of this study was to investigate the inhibition of K562 cancer cells line by oxidizing magnesium nanoparticles.   Methods: In an experimental study, three healthy volunteers were isolated and peripheral blood mononuclear cells were isolated. Cancer cells were prepared from the Pasteur Institute. Both cell typs were separately cultured with different concentrations of magnesium oxide nanoparticles (0, 25, 50, 100, 200 mg / l) for 24 hours. Then, the cytotoxicity effect was evaluated on tumor and normal cells by MTT (Tetrazolium Dye-Reduction Assay). Also, cancer cells stained with ochriddin and propodium iodide were studied. Data were analyzed by ANOVA and Tukey test..   Results: MgO NPs had no effects on cell viability of K562 cancer cells and peripheral blood mononuclear cell (normal cells) in MTT assay. The MgO NPs did not induce apoptosis which was confirmed through acridine orange and propidium iodide double staining. Conclusion: In this study, magnesium oxide nanoparticles in the concentrations and duration of exposure did not significantly affect the fecundity of K562 and normal PBMC blood cells.